Expert opinion on NSCLC small specimen biomarker testing - Part 2: Analysis, reporting, and quality assessment - Penault-Llorca, Frédérique; Kerr, Keith M; Garrido, Pilar; Thunnissen, Erik; Dequeker, Elisabeth; Normanno, Nicola; Patton, Simon J; Fairley, Jenni; Kapp, Joshua; de Ridder, Daniëlle; Ryška, Aleš; Moch, Holger (Virchows Archiv, 2022)
The diagnostic work-up for non-small cell lung cancer (NSCLC) requires biomarker testing to guide therapy choices. This article is the second of a two-part series. In Part 1, we summarised evidence-based recommendations for obtaining and processing small specimen samples (i.e. pre-analytical steps) from patients with advanced NSCLC. Here, in Part 2, we summarise evidence-based recommendations relating to analytical steps of biomarker testing (and associated reporting and quality assessment) of small specimen samples in NSCLC. As the number of biomarkers for actionable (genetic) targets and approved targeted therapies continues to increase, simultaneous testing of multiple actionable oncogenic drivers using next-generation sequencing (NGS) becomes imperative, as set forth in European Society for Medical Oncology guidelines. This is particularly relevant in advanced NSCLC, where tissue specimens are typically limited and NGS may help avoid tissue exhaustion compared with sequential biomarker testing. Despite guideline recommendations, significant discrepancies in access to NGS persist across Europe, primarily due to reimbursement constraints. The use of increasingly complex testing methods also has implications for the reporting of results. Molecular testing reports should include clinical interpretation with additional commentary on sample adequacy as appropriate. Molecular tumour boards are recommended to facilitate the interpretation of complex genetic information arising from NGS, and to collaboratively determine the optimal treatment for patients with NSCLC. Finally, whichever testing modality is employed, it is essential that adequate internal and external validation and quality control measures are implemented.
Keywords: Molecular diagnostics; Biomarkers; Next-generation sequencing; Best practice; Non-small cell lung carcinoma; Mutation; biologické markery; mutace; lidé; Liquid biopsy; nádory plic; Carcinoma, Non-Small-Cell Lung; Humans; nemalobuněčný karcinom plic; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; Lung Neoplasms; External quality assessment